The complete Node.js developer course - Percival, Rob (Packt Publishing, 2019)
"The Complete Node.js Developer Course covers the fundamentals of Node before diving deep into great tools like Express, Mongoose, and MongoDB. The entire course is based around a single goal: Turning you into a professional Node developer capable of developing, testing, and deploying real-world production applications. The best way to learn Node is by building Node apps. From the very start, you'll be programming every project and working through challenges that I've designed to reinforce what you've learned. This will give you the hands-on experience necessary to be able to create and launch your own project once you're done."--Resource description page